[ 6n + 8 ] is.
Chat with our AI personalities
8 + (74 x 6) = 75th term. nth term = 8 + 6(n-1)
t(n) = 10 - 6n where n = 1, 2, 3, ...
The nth term in this arithmetic sequence is an=26+(n-1)(-8).
The given sequence is an arithmetic sequence with a common difference of 6, as each term increases by 6. To find the nth term of an arithmetic sequence, we use the formula: nth term = a + (n-1)d, where a is the first term, d is the common difference, and n is the term number. In this case, the first term a = 2, the common difference d = 6, and the term number n is not specified. Therefore, the nth term of the sequence 2, 8, 14, 20, 26 is 2 + (n-1)6.
Well, isn't that just a lovely pattern we have here? Each term is increasing by 4, isn't that delightful? So, if we want to find the nth term, we can use the formula: nth term = first term + (n-1) * common difference. Just like painting a happy little tree, we can plug in the values and find the nth term with ease.